The religious attitude within psychological hardiness attachment styles among students who appeal for divorce - Bahman Akbari (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Family is the most important establishment according Islamic religion. On the other hand, life attachment styles could effect on quality of family establishment and marriage. Psychological hardiness is a critical component and could regulate helplessness of stress and family problems. Objective: The purpose of this study was to determine relationship between religious attitude and psychological hardiness attachment styles among students who signed for divorce in Rasht. Methods: This descriptive- correlational study was conducted on 196 (98 couples) individual who married at least for 2 - 10 years (one of them was student), and during the second half of the year 91 (last 6 months of the year) they referred to family court in Rasht. The samples were selected by simple random sampling. Then questionnaires about Religious Attitude Adult Attachment Styles and Psychological hardiness were completed by individuals. Data were analyzed using multiple regression correlation and multiple regressions (canonical correlation). Results: The study showed correlation between religious attitudes and psychological hardiness attachment styles of divorcing couples (P <0/05). In other words all dimensions between religious attitudes and psychological hardiness did not showed significant correlation (P <0/01), except for ceremonial aspects, all aspects of the relationship between religious attitude with style anxiety was not significant. Also In this study, the highest correlation between closeness and attachment style were observed (P <0/01, r= 0/675). Conclusion: The findings of this study have shown that, the religious attitude attachment styles among spouses could be predicted. This means that if spouses improve their religious attitude, it may improve secure attachment in between. On the other hands empowerment of religious attitudes among couples decreases their psychological hardiness.